Design of Customer Satisfaction E-Questionnaire and Chatbot System at PT. PLN (Persero) Bengkulu City Website Based - Rozali Toyib; Yuza Reswan; Pahrizal Pahrizal; Feby Ayu Sahputry (Penerbit Jurnal Indonesia, 2022)
Customer satisfaction is a form of feeling happy or disappointed someone who comes from a comparison between his impression of the performance of a service or goods against his expectations. PT PLN (Persero) Bengkulu City in the implementation of the implementation of the provision of electricity services certainly does not escape the existence of problems. The problems that arise are regarding customer complaints about the services provided by the problematic company. Seeing from these problems the solutions that can be given to overcome their complaints, it is very suitable to make an e-questionnaire system and chat customer complaints process using a website-based chatbot. This system will apply the Likert scale calculation method as a method to measure the level of customer satisfaction which will make it easier to get the results of filling out the questionnaire. In addition, this system will later create a complaint chat using a chatbot, which is a robotic chat service with artificial intelligence or AI (Artificial Intelligent) that imitates human conversations through messages that will answer customer questions regarding service problems provided by the company. This will certainly make it much easier for the company to get results from filling out questionnaires and make it easier for customers to make complaints regarding problems with the services provided. The results of this study have created an E-Questionnaire system for Customer Satisfaction and a website-based Complaint Chatbot.